2019
DOI: 10.1016/j.chaos.2018.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and revival of oscillations through time-varying interaction

Abstract: We explore the dynamical consequences of switching the coupling form in a system of coupled oscillators. We consider two types of switching, one where the coupling function changes periodically and one where it changes probabilistically. We find, through bifurcation diagrams and Basin Stability analysis, that there exists a window in coupling strength where the oscillations get suppressed. Beyond this window, the oscillations are revived again. A similar trend emerges with respect to the relative predominance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The stability of synchronized state in time-varying networks is also explored by Kohar et al [16]. Suppression and revival of oscillations were observed by switching the coupling form in a system of coupled oscillators [17]. Moreover, the study of the spread of epidemics in timevarying networks leads to the result that if the network changes more rapidly, the disease cycle becomes more synchronized which denotes the beginning of epidemics in the system [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of synchronized state in time-varying networks is also explored by Kohar et al [16]. Suppression and revival of oscillations were observed by switching the coupling form in a system of coupled oscillators [17]. Moreover, the study of the spread of epidemics in timevarying networks leads to the result that if the network changes more rapidly, the disease cycle becomes more synchronized which denotes the beginning of epidemics in the system [18].…”
Section: Introductionmentioning
confidence: 99%
“…In all these existing studies, the interaction or coupling among the systems is constant over time. However, the strength or form of interaction between systems can vary with time [12][13][14][15][16][17][18][19][20]. In such cases, it is important to study the global behavior of the coupled systems which depends on the interplay between the variable strength of dynamic interaction and switching frequency between dynamic interaction strengths.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of dynamic interaction has been recognized already by considering few general frameworks on the interacting nonlinear oscillators, where either the interacting function is changing over time [18][19][20][21] , or the interaction depends on the states of the individual oscillators [22][23][24] . In this article, we consider a new form of dynamic mean-field interaction with two distinct possible variations.…”
Section: Introductionmentioning
confidence: 99%
“…Information diffusion over communication networks, data packet transmission on the web, disease contagion on the social network of patients are perhaps few potential examples, which attest the fundamental necessity of the temporal network approach [28,29]. Such time-varying interactions among coupled oscillators give rise to fascinating collective phenomena [30][31][32][33][34][35][36][37][38]. Earlier, Majhi et al [39] reported the emergence of death state in a temporal network of mobile oscillators.…”
mentioning
confidence: 99%